2018
DOI: 10.1098/rspb.2018.0978
|View full text |Cite
|
Sign up to set email alerts
|

Ancient DNA reveals the chronology of walrus ivory trade from Norse Greenland

Abstract: The importance of the Atlantic walrus ivory trade for the colonization, peak, and collapse of the medieval Norse colonies on Greenland has been extensively debated. Nevertheless, no studies have directly traced medieval European ivory back to distinct Arctic populations of walrus. Analysing the entire mitogenomes of 37 archaeological specimens from Europe, Svalbard, and Greenland, we here discover that Atlantic walrus comprises two monophyletic mitochondrial (MT) clades, which diverged between 23 400 and 251 1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 71 publications
4
44
0
Order By: Relevance
“…Analyses requiring destructive sampling can give valuable insights into important research fields, such as domestication, development of livestock breeds, ritual activity and trade, and contribute to the preservation of local livestock breeds and endangered species (e.g. [5,6,21,23,26,7783]). However, these analyses are most fruitful when done on archaeofaunal collections which have already been analysed with traditional zooarchaeological methods [7,23,32,45].…”
Section: Destructive Sampling Of Archaeofaunal Materialsmentioning
confidence: 99%
“…Analyses requiring destructive sampling can give valuable insights into important research fields, such as domestication, development of livestock breeds, ritual activity and trade, and contribute to the preservation of local livestock breeds and endangered species (e.g. [5,6,21,23,26,7783]). However, these analyses are most fruitful when done on archaeofaunal collections which have already been analysed with traditional zooarchaeological methods [7,23,32,45].…”
Section: Destructive Sampling Of Archaeofaunal Materialsmentioning
confidence: 99%
“…ancient or historic ivory artifacts or remains), as it has been demonstrated that the use of PCR with degraded DNA may produce false-negative (non-amplifiable DNA template), as well as false-positive results (contamination biases) 27 and references therein. One of the main advantages of shotgun sequencing in archaeogenetics is that it allows to obtain ancient/historic DNA signature patterns 10 , 31 and also to observe putative contaminated reads, as well as postmortem deamination-related misincorporated nucleotides and sequencing errors on sites covered by overlapping sequences, allowing to minimize their introduction into the final datasets. On the other hand, one of the main disadvantages of the method used in the present study is that it limits down the provenance of the sample only to regional areas or countries as it massively depends on the resolution power of mtDNA and the current mtDNA elephant phylogeography.…”
Section: Discussionmentioning
confidence: 99%
“…Genome-skimming, also known as low-coverage whole-genome shotgun sequencing is a cost-effective technique, capable to recover high-copy parts of total genomic DNA, such as organellar genomes, at low sequence depth 7 , 8 . This method has been proven efficient for species identification and phylogenetic studies on centuries-old museum samples 9 and references therein, as well as on raw walrus ivory material 10 . This type of biological material display characteristics of ancient DNA (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Although our samples represent a large region and a broad time scale, it is likely that this overrepresentation of males reflect some overall degree of prey selection. Prehistoric hunting with a focus on achieving large amounts of ivory (Star et al, 2018;Pierce, 2009;Frei et al, 2015) might have primarily targeted larger dominant males, whose tusks in general are longer and thicker than the female tusks (Kastelein, 2009). While such a hunting practice would explain the skewed sex ratio, such patterns should, however, be further examined on a more fine-scaled level within each regional and cultural context.…”
Section: Implications For Understanding Human Hunting Practice and Pimentioning
confidence: 99%